Frankincense preparation promotes formation of inflammation-resolving lipid mediators by manipulating lipoxygenases in human innate immune cells - Nischang, Vivien; Witt, Finja M.; Börner, Friedemann; Gomez, Mario; Jordan, Paul M.; Werz, Oliver (Frontiers in Pharmacology, 2024)
Frankincense preparations are frequently used as traditional anti-inflammatory remedies in folk medicine with increasing popularity. Boswellic acids (BAs), especially 3-O-acetyl-11-keto-βBA (AKBA), are unique anti-inflammatory principles of frankincense, with multiple pharmacological actions and target proteins. We recently showed that AKBA favorably impacts lipid mediator (LM) networks in innate immune cells, by modulation of lipoxygenase (LOX) activities. Thus, AKBA binds to allosteric sites in 5-LOX, shifting the regiospecificity to a 12/15-lipoxygnating enzyme, and to an analogous site in 15-LOX-1, leading to enzyme activation, which favors specialized pro-resolving mediator (SPM) formation at the expense of leukotriene production. Here, we investigated Boswellin super® (BSR), a commercially available frankincense extract with ≥30% AKBA, used as remedy that approved efficacy in osteoarthritis trials, for its ability to modulate LM pathways in human monocytederived macrophage (MDM) phenotypes, neutrophils, and neutrophil/platelet co-incubations. BSR concentration-dependently (10 -100 µg/ml) suppressed formation of pro-inflammatory 5-LOX products including LTB4 in exotoxin-stimulated M1-MDM and neutrophils, and strongly elevated 12/15-LOX products and SPM in activated M2-MDM and neutrophil/platelet cocultures, starting at 10 µg/mL. Also, BSR (≥ 10 µg/mL) induced robust 12/15-LOX product and SPM generation in resting M2-MDM, which was further markedly elevated when exogenous docosahexaenoic acid (DHA) and eicosahexaenoic acid (EPA) were supplied, and induced translocation of 15-LOX from a soluble to a particulate locale in M2 MDM. In conclusion, BSR especially when co-added with DHA and EPA, promotes the LM class switch in innate immune cells from pro-inflammatory to pro-resolving mediators, which might be a plausible mechanism underlying the anti-inflammatory actions of BSR.